Parametric investigation on the aerodynamic characteristic of NACA2415 airfoil at low reynolds number - Muhammad Hafizuddin, Ismail (2013)
This study is to investigate the aerodynamic characteristic of an airfoil in low Reynolds number flow. NACA2415 airfoil is chosen as the test subject as it has been studied by many researches and documented. Coordinate point of NACA2415 is generated by using NACA 4 Digits Series Profile Generator, a web-based Java applet before being used by ANSYS Fluent to create 2D geometry of the airfoil. In the simulation, the boundary condition is set mimicking the streamline flowing at an angle ranging from 0 degree to 20 degree. As for the velocity, it is set for a flow condition under the Reynolds number of 200000 in incompressible viscous medium. From the simulation data, the Cd, Cl, Cp and the formation of Laminar Separation Bubble becoming the main concern for the simulation. Validation test is performed to approve the validity of the simulation result. Unfortunately, this investigation comes to a hold since the validation test is failed to capture the formation of LSB. The factor leading to the error is discussed.